Inhibition of Type IV Secretion Activity and Growth of Helicobacter pylori by Cisplatin and Other Platinum Complexes - Lettl, Clara; Schindele, Franziska; Testolin, Giambattista; Bär, Alexander; Rehm, Tobias; Brönstrup, Mark; Schobert, Rainer; Bilitewski, Ursula; Haas, Rainer; Fischer, Wolfgang (Frontiers in Cellular and Infection Microbiology, 2020)
Type IV secretion systems are protein secretion machineries that are frequently used by pathogenic bacteria to inject their virulence factors into target cells of their respective hosts. In the case of the human gastric pathogen Helicobacter pylori, the cytotoxin-associated gene (Cag) type IV secretion system is considered a major cause for severe disease, such as gastric cancer, and thus constitutes an attractive target for specific treatment options against H. pylori infections. Here, we have used a Cag type IV secretion reporter assay for screening a repurposing compound library for inhibitors targeting this system. We found that the antitumor agent cisplatin, a platinum coordination complex that kills target cells by formation of DNA crosslinks, is a potent inhibitor of the Cag type IV secretion system. Strikingly, we found that this inhibitory activity of cisplatin depends on a ligand exchange reaction which incorporates a solvent molecule (dimethylsulfoxide) into the complex, a modification which is known to be deleterious for DNA crosslinking, and for its anticancer activity. We extended our analysis to several analogous platinum complexes containing N-heterocyclic carbene, as well as DMSO or other ligands, and found varying inhibitory activities toward the Cag system which were not congruent with their DNA-binding properties, suggesting that protein interactions may cause the inhibitory effect. Inhibition experiments under varying conditions revealed effects on adherence and bacterial viability as well, and showed that the type IV secretion-inhibitory capacity of platinum complexes can be inactivated by sulfur-containing reagents and in complex bacterial growth media. Taken together, our results demonstrate DNA binding-independent inhibitory effects of cisplatin and other platinum complexes against different H. pylori processes including type IV secretion.